AVALIAÇÃO DO EFEITO CICATRIZANTE DE FILMES DE ALGINATO CONTENDO GEL DE BABOSA - Aloe vera (L.) Burm. f. - Koga, Adriana Yuriko (2017)
Alginate is a polymer extracted from seaweed and traditionally used in various types of wound dressings. It is a polysaccharide which has bioadhesive and swelling characteristics. The ability of alginate to form gel and films provides a favorable environment for healing and re-epithelialization of the injured tissue. Aloe vera (L.) Burm. f., or simply Aloe, is a medicinal plant with analgesic, anti-inflammatory and healing properties. The purpose of this study was to develop an alginate film containing Aloe gel and examine its cutaneous healing effect in vivo. The film was obtained by casting of the aqueous sodium alginate solution containing glycerin and Aloe gel, followed by crosslinking with calcium chloride. The film was characterized by mechanical tensile strength, hydration degree, FTIR spectroscopy, scanning electron microscopy, polysaccharide and calcium release. The wound healing effect was studied by performing surgical wounds in the back of Wistar rats. The animals (n = 60) were divided into three groups: gauze dressings (control), dressing with alginate film and dressing with alginate-aloe film. The retraction of wounds was measured every 3 days. On days 3, 7, 14, 22 five animals from each group were euthanized and samples of skin were removed and fixed in formalin 10%. The samples for histological analysis were stained with hematoxylin-eosin and analyzed for quantification of inflammatory infiltrate, angiogenesis and macrophages. Collagen fibers were evaluated using a picrosirius red staining for differentiation of type I and III fibers. The alginate-aloe film exhibited desirable physical and mechanical characteristics for the wound dressing application. In vivo animal test revealed there was no significant difference among the three groups in wound retraction. The results of histological analysis showed a beneficial effects of alginate-aloe (p=0.04) and alginate films (p=0.05) decreasing the inflammatory infiltrate at 14th days, in relation to the control group. On the 7th day, there was an increased angiogenesis in the control group compared to the group treated with alginate-aloe films (p = 0.04) and alginate (p = 0.024). Treatment with alginate-aloe film increased the number of blood vessels on the 14th day, when compared to the control group (p = 0.004); in addition, it caused decrease of macrophages on day 22, when compared to the other groups (alginate film (p = 0,0) and control (p = 0.007). The evaluation of the collagen fibers showed a significant difference between the alginate-aloe film and control group, with evident decrease of type III fibers (p = 0.05) and increase of type I fibers (p = 0.024) between days 14 and 22, suggesting an improvement in the progression of the healing process.